Subchondral Trabecular Microstructure and Articular Cartilage Damage Variations Between Osteoarthritis and Osteoporotic Osteoarthritis: A Cross-sectional Cohort Study - Zhou, Feng; Chu, Linyang; Liu, Xuqiang; He, Zihao; Han, Xuequan; Yan, Mengning; Qu, Xinhua; Li, Xiaofeng; Yu, Zhifeng (Frontiers in Medicine, 2021)
Osteoporotic osteoarthritis (OP-OA) is a specific type of OA. In this study, we aimed to assess the subchondral plate and rod microstructural differences between OA and OP-OA patients by using an individual trabeculae segmentation (ITS) system and to analyze the relationships between subchondral microstructures and cartilage damage in OA and OP-OA patients. Overall, 31 femoral heads were included in this study, which included 11 samples with OA and 13 samples with OP-OA; the normal control (NC) group contained 7 healthy femoral heads. ITS was performed to segment the subchondral trabecular bone into plate and rod trabeculae based on microcomputed tomography (micro-CT) images. We compared the plate and rod trabeculae of the subchondral trabecular bone between OA and OP-OA patients. The Osteoarthritis Research Society International (OARSI) score was employed to evaluate cartilage damage based on histological observations. Pearson’s correlation coefficient and linear regression analysis were applied to analyze the relationships between subchondral microstructures and articular cartilage damage. Results showed that several microstructural parameters, including bone volume fraction (BV/TV), plate bone volume fraction (pBV/TV), rod bone volume fraction (rBV/TV), plate trabecular number (pTb.N), rod trabecular number (rTb.N), junction density between rod and plate (R-P Junc.D), and junction density between plate and plate (P-P Junc.D), were significantly decreased in patients with OP-OA compared with those in patients with OA (p<0.05). Histological observations indicated that cartilage damage was more serious in patients with OP-OA than that in patients with OA (p<0.05). Moreover, BV/TV, pBV/TV, pTb.N, and pTb.Th were significantly related to the OARSI score in both OA and OP-OA patients. These results indicated that there were differences in the subchondral rod and plate trabeculae between OA and OP-OA patients. Subchondral decreased plate trabeculae (pBV/TV, pTb.N, and pTb.Th) might account for cartilage damage in the progression of OP-OA. This study provided new insights to research OA when it is combined with OP.